PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA LINGKUNGAN (Studi pada Perusahaan yang memperoleh PROPER) - Lena Supriati Sihombing; Anis Chariri (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of ownership structure on the performance of the environment. Ownership structure used in this study is managerial ownership, institutional ownership, foreign ownership and public ownership. Environmental performance assessed using PROPER issued by the Ministry of Environment. The analytical method used is the ordinal regression using SPSS. The method of selecting samples using purposive sampling in companies that are listed in Indonesia Stock Exchange and PROPER in 2010-2012. The structure of managerial ownership, institutional ownership and public ownership is measured from the percentage shareholding companies while foreign ownership is measured by a dummy variable. The results showed that foreign ownership variables significantly influence environmental performance. Variable managerial ownership, institutional ownership and public ownership does not have a significant influence on the performance of the environment.